Effects of reducing free sugars on 24-hour glucose profiles and glycemic variability in subjects without diabetes - Pappe, Christina Laeticia; Peters, Beeke; Dommisch, Henrik; Woelber, Johan Peter; Pivovarova-Ramich, Olga (Frontiers in Nutrition, 2023)
The western diet, especially beverages and high processed food products, is high in sugars which are associated with the development of obesity and diabetes. The reduction of refined carbohydrates including free and added sugars improves glycemic control in individuals with diabetes, but the data regarding effects in subjects without diabetes are limited.The aim of this study was to evaluate the effects of reducing free sugar intake on 24-hour glucose profiles and glycemic variability using continuous glucose monitoring (CGM).In the randomized controlled study, 21 normal-weight and overweight/obese subjects (BMI 18-40kg/m 2 ) without diabetes were assigned to a four-week reduced-sugar (RS) diet or control diet2 This is a provisional file, not the final typeset article after a two-week baseline phase. During the baseline phase, all participants were advised not to change their habitual diet. During the intervention phase, RS participants were asked to avoid added sugar and white flour products, whereas participants of the control group were requested to proceed their habitual diet. Anthropometric parameters and HbA1c were assessed before and at the end of the intervention phase. Interstitial glucose was measured using continuous glucose monitoring (CGM), and the food intake was documented by dietary records for 14 consecutive days during the baseline phase and for the first 14 consecutive days during the intervention phase. Mean 24-hour glucose as well as intra-and inter-day indices of glucose variability, i.e. standard deviation (SD) around the sensor glucose level, coefficient of variation in percent (CV), mean amplitude of glucose excursions (MAGE), continuous overlapping net glycemic action (CONGA), and mean absolute glucose (MAG) were calculated for the baseline and intervention phases.Results: During the intervention, the RS group decreased the daily intake of sugar (-22.4 ± 20.2 g, i.e. -3.28 ± 3.61 EN%), total carbohydrates (-6.22 ± 6.92 EN%), total energy intake (-216 ± 108 kcal) and increased the protein intake (+2.51 ± 1.56 EN%) compared to the baseline values, whereby this intervention-induced dietary changes differed from the control group. The RS group slightly reduced body weight (-1.58 ± 1.33 kg), BMI, total fat and visceral fat content, and increased muscle mass...